2021
DOI: 10.1002/lrh2.10263
|View full text |Cite
|
Sign up to set email alerts
|

A learning health systems approach to integrating electronic patient‐reported outcomes across the health care organization

Abstract: Introduction: Foundational to a learning health system (LHS) is the presence of a data infrastructure that can support continuous learning and improve patient outcomes.To advance their capacity to drive patient-centered care, health systems are increasingly looking to expand the electronic capture of patient data, such as electronic patient-reported outcome (ePRO) measures. Yet ePROs bring unique considerations around workflow, measurement, and technology that health systems may not be poised to navigate. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
(56 reference statements)
0
8
0
2
Order By: Relevance
“…Functionality for automatic sampling and storage of data about the health problem, the care that is provided and the care outcomes [3], [20], [21].…”
Section: Learning Health System Feature or Functionality Possible Ind...mentioning
confidence: 99%
“…Functionality for automatic sampling and storage of data about the health problem, the care that is provided and the care outcomes [3], [20], [21].…”
Section: Learning Health System Feature or Functionality Possible Ind...mentioning
confidence: 99%
“…Despite the value of PROMs within a health system, their successful implementation into routine clinical care is complex (17,18). It requires a signi cant investment of time and resources, as well as the development of a supportive information technology infrastructure (17,19). Commonly cited challenges to their implementation include nding appropriate PROMs (i.e., relevant to patients' needs, feasible to use, and adding value to the clinical encounter), designing PROMs data collection processes around clinical work ows, getting buy-in from clinical staff, and creating a culture that is supportive of learning and quality improvement (17).…”
Section: Introductionmentioning
confidence: 99%
“…Systematically analyzing and translating health system data in the dynamic knowledge generation and exchange ecosystem of a learning health system (LHS) 1 , 2 , 3 can optimize health system productivity and improve patient outcomes. 4 , 5 , 6 , 7 After the Institute of Medicine first introduced the idea of an LHS in 2007 as applying available evidence to increase system effectiveness and efficiency, 2 various conceptual frameworks have been described in the literature. 1 , 6 , 8 , 9 Since then, the LHS concept has become widely accepted and acknowledged globally.…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 13 However, those who have evaluated the process, outcomes, and impacts of LHS programs have demonstrated that an LHS can improve program development, patient outcomes, as well as time and cost‐effectiveness. 1 , 6 , 7 , 11 , 14 , 15 Evaluating an LHS encourages continuous system improvement and collaboration within the healthcare system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation